Structural and Dielectric Properties of Polycrystalline Calcium Copper Titanate (CCTO) - Mohammed, J.; Garba, Isah I.; Yerima, K. U.; Muhammad, Aminu; Zulfatu, U. F.; Abubakar, Mubarak S.; Sharma, Jyoti (Springer Nature, 2018)
Polycrystalline calcium copper titanate (CCTO) with chemical composition Ca1- xCexCu3Ti4-yNi yO12 (x = 0.0, 0.25, 0.45, 0.65 and y = 0.0, 0.3, 0.5, 0.7) was synthesized via sol-gel technique. The prepared samples were subjected to pre-sintering in a muffle furnace at 800 ? for 6 h and thereafter sintered at 900 ? for 6 h. XRD analysis confirmed the formation of calcium copper titanate with traces of CaTiO3 and CuO whose intensity increases with substation of Ce–Ni. HRSEM micrograph shows large, regular and polyhedral grains with size ranging from 902.4 nm to 1.562 ?m. EDX spectra shows presence of elements in agreement with the stoichiometry of the prepared sample. High value of dielectric constant (16,000 at 100 Hz) was observed in the sample with x = 0.25 and y = 0.3 at low frequency. The sample with x = 0.65 and y = 0.7 exhibit the lowest dielectric tangent loss (0.189). Cole-Cole plot indicates that the dielectric properties of the prepared sample mostly result from grain boundary resistance. © 2018, Springer International Publishing AG, part of Springer Nature.
Keywords: AC conductivity; Cole-Cole plot; Dielectric constant; Dielectric loss